IMPROVING ENGLISH SPEAKING SKILLS USING THE COMMUNICATION LANGUAGE TEACHING (CLT) METHOD THROUGH WEBSITE-BASED APPLICATIONS - Latifatul; Yani Octafia; Kiki Kaherunisa (LPPM Universitas PGRI Jombang, 2026)
This study aims to improve junior high school students’ English speaking skills through the application of the Communicative Language Teaching (CLT) method integrated with the web-based application Duolingo. The study addresses students’ low speaking proficiency caused by limited innovative learning media and insufficient opportunities for communicative practice. A pre-experimental one-group pretest–posttest design was employed involving 10 students of eighth-grade students. Over a three-week period, students participated in speaking activities supported by Duolingo’s interactive features aligned with CLT principles. The results indicated significant improvement in students’ speaking skills, particularly in pronunciation, fluency, grammar, and vocabulary. Post-test scores showed that most students achieved high results, with several reaching the maximum score. Improvements were most notable in grammar and vocabulary, while pronunciation and fluency developed positively. In addition, students demonstrated increased motivation and confidence in speaking English. Overall, the findings suggest that integrating CLT with Duolingo is an effective and engaging approach to enhance students’ speaking skills in the digital learning era.